THE DEPICTIONS OF ANIMAL SUFFERING IN THE NEWEST POLISH AND RUSSIAN WOMEN’S POETRY - Kwiatkowska, Agnieszka (Porównania, 2018)
The crisis of hermeneutics and the turnabout in anthropological research are conducive to the development of non-anthropocentric, post-humanist perspective and the reconstruction of the animal viewpoint and experience in animal literature, among others, suffering. The most recently published Polish women’s poetry (among others by Justyna Bargielska and Wisława Szymborska) portrays animals as the victims of human oppression and beings similar to humans. Empathy is often accompanied by anthropomorphism. In the women’s poetry written in Russian, the motif of animal suffering appears rather infrequently. A global (not individual) perspective dominates in poems, while the category of suffering is reserved for the collectivity (society or nation). Suffering is a human and not animal trait in the poetry of Olga Siedakowa, Regina Dieriewa, Lubow Salomon, Olga Lewicka and others.